Design and Development of Multifunctional Stretcher - S.S. Nirgude; S.N. Sabale; S.G. Kulkarni; S.S. Labhade; V.J. Suryawanshi (International Journal of Industrial and Product Design Engineering, 2026)
Hospital stretchers and wheelchairs are integrated in this piece. Instead of using the chair and stretcher individually, the suggested stretcher can be utilized for multiple purposes. Patients' mobility issues can be greatly reduced by this arrangement. There is a challenge in the ICU moving seriously damaged or fractured patients from stretcher to wheelchair. This product is capable of addressing such situations. One more advantage of the proposed design to conduct the tests like ECG & SCAN, without shifting the patient from stretcher to wheelchair. The current design also accommodates the provision of carrying accessories like oxygen cylinder and electronic blood pressure measuring machines. In addition to improving patient comfort, the integrated stretcher-wheelchair system significantly enhances safety during intra-hospital transport. By eliminating repeated patient transfers, the risk of secondary injuries, discomfort, and musculoskeletal strain to healthcare staff is substantially reduced. The transformation mechanism is designed to be smooth and controlled, allowing caregivers to convert the stretcher into a seated wheelchair configuration with minimal physical effort and without disturbing the patient’s posture. The ergonomic design includes adjustable backrest inclination, leg support elevation, and secure locking mechanisms to ensure stability during both stationary and mobile conditions. High-quality caster wheels with braking systems provide controlled movement across different hospital surfaces, including ramps and narrow corridors. Safety features such as side rails, patient restraint belts, and shock-absorbing frames further enhance reliability, particularly in critical care environments like the ICU and emergency wards. From a clinical perspective, the ability to perform diagnostic procedures such as ECG, scanning, and routine monitoring directly on the integrated unit improves workflow efficiency and reduces waiting time. The built-in mounting brackets for oxygen cylinders, infusion stands, and monitoring devices ensure uninterrupted care during transport. This continuity is especially beneficial for critically ill or trauma patients who require constant observation and life-support equipment.
Keywords: Mechanism; Stretcher; design features; mobility; multi-purpose; wheel chair